Demographic profile of children with acute lower respiratory tract infections of age between 2months to 5 years - Dr. Vinod Kumar Gornale; Dr. Naikey Minarey; Dr. Amitoj Singh Chhina; Dr.Nagendra Katwe; Dr. Harsha P.J; Dr.Chandrakala Iyer (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Acute respiratory infections are a leading cause of morbidity and mortality in under-five children in developing countries. Hence, the present study was undertaken to study the various demographic risk factors which predispose to acute lower respiratory tract infections (ALRI) in children aged 2 month to 5 year. Objective; Demographic factors associated with acute lower respiratory tract infections in children aged 2 months to 5 years. Methods: 100 ALRI cases fulfilling WHO criteria for pneumonia, in the age group of 2 month to 5 years were evaluated for demographic risk factors and clinical profile as per a predesigned proforma in a rural medical college. Results: Socio-demographic risk factors like parental illiteracy, overcrowding, partial immunisation and low socioeconomic status were potential risk factors; similarly nutritional risk factors like early and late weaning, anaemia and malnutrition were associated with ALRI. Significant environmental risk factors were use of biomass fuels, inadequate ventilation at home, and lack of separate kitchen. Conclusion: The present study has identified various socio-demographic, nutritional and environmental risk factors for ALRI which can be tackled by effective health education of the community and effective training of peripheral health personnel.